Estudio de impacto: programa Escuela para jóvenes (período 2001 - 2007) - Larrovere, Cecilia; Calneggia, María Isabel; Di Francesco, Adriana; Monteverdi, Griselda; Coschica, Jorge; García, Paulo; Lázaro, Lucas; Furlán, Silvia (Anuario Digital de Investigación Educativa, 2019)
Ninguno